Effectiveness of Consumption of Brown Rice and Potatoes in Reducing Blood Sugar in the Elderly with Type 2 Diabetes Mellitus at Pondok Ranji Health Center - Rahmawaty Rahmawaty; Achmad Fauzi (STIKep PPNI Jawa Barat, 2022)
Aims: Type 2 diabetes mellitus in the elderly is still the highest disease in Indonesia. Caused by the elderly cannot produce insulin in sufficient quantities or more. Glucose levels above 200 gr%. Brown rice and potatoes are staple food sources with a fairly high amount of carbohydrates and have lower glucose levels than white rice. Research Objectives: To determine the effectiveness of consumption of brown rice and potatoes in reducing blood sugar in the elderly with type 2 diabetes mellitus at Pondok Ranji Public Health Center, South Tangerang City. Research Methods: This study used a quasi-experimental with purposive sampling with a sample of 20 people. The data technique is included in the bivariate analysis using the SPSS program statistical calculations. Research Results: Based on the results of the study the average value of brown rice consumption in the elderly with type 2 diabetes mellitus was 64.45, and the average value of potato consumption in the elderly with type 2 diabetes was 47.21, the results of the statistical test p-value 0.02 < 0.05 Conclusions and Suggestions: There is a difference between the consumption of brown rice and potatoes in reducing blood sugar levels in the elderly with type 2 diabetes mellitus, where the results obtained on average are that brown rice is more effective in reducing blood sugar levels compared to potatoes.